2002
DOI: 10.1074/jbc.m203788200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Bacteria-binding Peptide Domain on Salivary Agglutinin (gp-340/DMBT1), a Member of the Scavenger Receptor Cysteine-rich Superfamily

Abstract: Salivary agglutinin is encoded by DMBT1 and identical to gp-340, a member of the scavenger receptor cysteine-rich (SRCR) superfamily. Salivary agglutinin/ DMBT1 is known for its Streptococcus mutans agglutinating properties. This 300 -400 kDa glycoprotein is composed of conserved peptide motifs: 14 SRCR domains that are separated by SRCR-interspersed domains (SIDs), 2 CUB (C1r/C1s Uegf Bmp1) domains, and a zona pellucida domain. We have searched for the peptide domains of agglutinin/DMBT1 responsible for bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
183
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 147 publications
(194 citation statements)
references
References 39 publications
8
183
3
Order By: Relevance
“…This shows that both gp-340 and CRP-ductin are cable of binding bacteria in the absence of SP-D, indicating that these molecules could have a role in the microbial clearance of potentially pathogenic microorganisms alone or in combination with SP-D. The binding site of the agglutinin-bacteria interaction has recently been mapped to a SRCR domain [28], making it likely that its also a SRCR domain in CRP-ductin that interacts with bacteria.…”
Section: Discussionmentioning
confidence: 95%
“…This shows that both gp-340 and CRP-ductin are cable of binding bacteria in the absence of SP-D, indicating that these molecules could have a role in the microbial clearance of potentially pathogenic microorganisms alone or in combination with SP-D. The binding site of the agglutinin-bacteria interaction has recently been mapped to a SRCR domain [28], making it likely that its also a SRCR domain in CRP-ductin that interacts with bacteria.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, it has been suggested that the frequency of high copy number alleles of the salivary amylase gene AMY1 has increased by natural selection in populations that eat a carbohydrate-rich diet (20). DMBT1 SAG mostly consists of an array of scavenger receptor cysteine-rich (SRCR) domains which bind bacteria, including S. mutans (21) and promote their adherence to hydroxyapatite of the tooth (22,23), which is critical for the cariogenic activity of the bacteria. The canonical DMBT1 gene annotated in the hg19 human genome assembly has 13 repeats each containing a SRCR domain (Fig.…”
Section: Significancementioning
confidence: 99%
“…Inhibition of gp340 Binding-Both the carbohydrate portions of gp340 and its peptide core have been reported to mediate microbial binding (18,32). In order to characterize the structures involved in Spy0843 binding, we first tested the effects of various monosaccharides and treatments affecting the glycopart of gp340 on r0843 binding.…”
Section: Inhibition Of S Pyogenes Binding To Gp340 By Lrr Proteins-mentioning
confidence: 99%